1971
DOI: 10.1042/bj1210049
|View full text |Cite
|
Sign up to set email alerts
|

Activities of enzymes of ketone-body utilization in brain and other tissues of suckling rats

Abstract: 1. The activities of 3-hydroxybutyrate dehydrogenase and 3-oxo acid CoA-transferase in rat brain at birth were found to be about two-thirds of those of adult rat brain, expressed per g wet wt. The activities rose throughout the suckling period and at the time of weaning reached values about three times higher than those for adult brain. Later they gradually declined. 2. At birth the activity of acetoacetyl-CoA thiolase in rat brain was about 60% higher than in the adult. During the suckling period there was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
134
4
1

Year Published

1974
1974
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(158 citation statements)
references
References 14 publications
(12 reference statements)
19
134
4
1
Order By: Relevance
“…Because total glucose utilization was not measured in the present study, we cannot say whether the reduction in V pdhN with increasing V AcCoA-kbN corresponded to reduced or unchanged glucose utilization (e.g., net lactate formation followed by efflux). Reduced brain glucose utilization and increased lactate efflux is seen during prolonged fasting-induced hyperketonemia in humans 32 and rats, 27 suggesting that a larger glycolytic component than we estimate based on pyruvate oxidation during maximum ketone use, cannot be fully excluded.…”
Section: Implications Of Ketone Body Oxidation For Models Of Neuroenementioning
confidence: 80%
“…Because total glucose utilization was not measured in the present study, we cannot say whether the reduction in V pdhN with increasing V AcCoA-kbN corresponded to reduced or unchanged glucose utilization (e.g., net lactate formation followed by efflux). Reduced brain glucose utilization and increased lactate efflux is seen during prolonged fasting-induced hyperketonemia in humans 32 and rats, 27 suggesting that a larger glycolytic component than we estimate based on pyruvate oxidation during maximum ketone use, cannot be fully excluded.…”
Section: Implications Of Ketone Body Oxidation For Models Of Neuroenementioning
confidence: 80%
“…This is consistent with the unique developmental pattern of the ketone-body-metabolizing enzymes. The activity of these enzymes is relatively high at birth, increases about 3-5-fold and then declines at weaning to the adult level [4,5]. This is in contrast with the development of other mitochondrial enzymes, whose activities increase gradually from a low level at birth to the adult level during the first 3 weeks.…”
Section: Introductionmentioning
confidence: 53%
“…The recombinant plaques were screened with a 1: 1500 dilution of a specific polyclonal antibody to rat brain 3-oxoacid CoAtransferase [4] from which antigenic determinants to E. coli and coliphage A proteins were removed on an affinity column of E. coli lysate from BNN 97 linked to CNBrtreated Sepharose 4B [9]. Positive plaques containing 3-oxoacid CoA-transferase determinants were identified with peroxidase-conjugated goat anti-(rabbit IgG) [10].…”
Section: Methodsmentioning
confidence: 99%
“…The ability of the brain to use ketone bodies is not believed to be an enzymic adaptation, as the 216 [9]. Changes in the activity of STK in diabetes have not previously been studied, though it has been suggested that the availability of succinyl-CoA could control ketone body utilization [ 10,111.…”
Section: Resultsmentioning
confidence: 99%